The diabetes solution : how to control type 2 diabetes and reverse prediabetes using simple diet and lifestyle changes - Rodríguez C., Jorge E. (Ten Speed Press, 2014)
"An authoritative guide to preventing, reversing, and managing prediabetes and diabetes, featuring a comprehensive and holistic diet, fitness, and lifestyle plan, along with 100 recipes, from the authors of The Acid Reflux Solution. The Diabetes Solution provides a complete program for fighting type 2 diabetes--and preventing prediabetes from developing into full-blown diabetes--by presenting the latest scientifically validated information on what exactly the disease is, how it progresses, and how it can be effectively treated. Because many studies prove that a minor weight loss of 5 to 7 percent can make a huge difference in blood sugar levels and diabetic status, this straightforward program also includes 100 delicious and easy-to-prepare recipes as part of The Blood Sugar Budget, a simplified eating plan that controls carb consumption, limits calories, and encourages weight loss. Proper management of diabetes from the earliest stages is essential; The Diabetes Solution simplifies the data, takes an aggressive stance on early medication, and focuses on reducing permanent damage and eliminating future complications so the newly diagnosed and those at risk can conquer the disease and thrive"--